2018
DOI: 10.1159/000488492
|View full text |Cite
|
Sign up to set email alerts
|

Animal Models of Proliferative Vitreoretinopathy and Their Use in Pharmaceutical Investigations

Abstract: Animal models are indispensable for pharmaceutical investigations. However, investigators often have difficulty choosing the appropriate modal for their research. To provide a comprehensive and convenient source of information about animal models of proliferative vitreoretinopathy (PVR), the current review sorted and analyzed representative animal models for pharmacotherapy of PVR since 1976.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 81 publications
1
11
0
Order By: Relevance
“…Compared with treatments with a single growth factor or cytokine or their combination, vitreous treatment is more relevant to an in vivo environment for PVR development (31)(32)(33)(34). In addition, rabbits are usually used to induce PVR (15,(34)(35)(36) because the smaller size of the rabbit lens as compared with that of the eyeball permits manipulations to be performed within the eye, without causing any damage to the lens and retina; however, other common laboratory animals such as rats and mice are difficult to work with because of the small volume of vitreous (20,37,38). Therefore, ARPE-19 cells were treated with normal vitreous from experimental rabbits (RV) for 2 h based on a previously established time course (16).…”
Section: Depletion Of P110␦ Attenuates Vitreous-induced Activation Ofmentioning
confidence: 99%
“…Compared with treatments with a single growth factor or cytokine or their combination, vitreous treatment is more relevant to an in vivo environment for PVR development (31)(32)(33)(34). In addition, rabbits are usually used to induce PVR (15,(34)(35)(36) because the smaller size of the rabbit lens as compared with that of the eyeball permits manipulations to be performed within the eye, without causing any damage to the lens and retina; however, other common laboratory animals such as rats and mice are difficult to work with because of the small volume of vitreous (20,37,38). Therefore, ARPE-19 cells were treated with normal vitreous from experimental rabbits (RV) for 2 h based on a previously established time course (16).…”
Section: Depletion Of P110␦ Attenuates Vitreous-induced Activation Ofmentioning
confidence: 99%
“…PVR is the leading cause of retinal detachment surgery failure and to date, despite significant advances in vitreoretinal surgery, it remains without an effective prophylactic or therapeutic medical treatment 60 . In this study, we identified RUNX1 as a mediator of EMT in PVR.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, rabbits are widely used in research to test pharmacologic efficacy, predictability, ocular safety and tolerability of new drugs and drug delivery devices due to anatomic and physiological similarities with human eyes 61,62 . Previous animal models of PVR have used surgical manipulation or injection of dermal fibroblasts or transformed cell lines to identify candidate treatments but to date these have not translated into effective therapies 21,39,60 . Using our rabbit model, we showed that topical application of a nanoemulsion containing a RUNX1 inhibitor effectively reduced progression of PVR.…”
Section: Discussionmentioning
confidence: 99%
“…Different animal species have been used to model PVR, each with its own pros and cons. 12 For example, rabbit models have the advantage of large vitreous volume and relative ease of manipulation with less risk of damage to the lens and retina compared to smaller animals such as the rat. However, their retinal structure, including blood vessels and nerve fiber distribution, differs from that of humans, complicating direct comparison to the human disease in anatomic and pathologic terms.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous RPE cells ( Table 3 ) are useful in animal models of PVR because it is difficult to release endogenous RPE cells in sufficient quantity to trigger the PVR process. 12 Umazume et al 7 described a porcine model of PVR in which injection of cadaveric porcine RPE cells successfully induced severe PVR in 14 out of 14 eyes after 14 days. However, exogenous RPE cell injections have a few issues, including the difficulty of keeping these cells viable, the risk of infection, and the possibility that these exogenous cells may trigger an immune-mediated rejection response.…”
Section: Discussionmentioning
confidence: 99%